2022
DOI: 10.1002/ueg2.12216
|View full text |Cite
|
Sign up to set email alerts
|

Close follow‐up is associated with fewer stricture formation and results in earlier detection of histological relapse in the long‐term management of eosinophilic esophagitis

Abstract: Background and aims:No recommendations exist regarding optimal follow-up schedule in patients with eosinophilic esophagitis (EoE) under maintenance treatment. Methods:We retrospectively evaluated a long-term surveillance concept at the Swiss EoE clinic, where clinical, endoscopic and histological disease activity is assessed annually regardless of EoE symptoms. Data on 159 adult patients under maintenance steroid treatment with available follow-up were analyzed. Patients were classified as having close (durati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…A recent study by Bon and colleagues analyzed long-term follow-up in the Swiss EoE cohort and found that absence of close follow-up, defined as a year or less, was associated with stricture develop after controlling for potential confounding factors. These data are also consistent with our findings [ 11 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A recent study by Bon and colleagues analyzed long-term follow-up in the Swiss EoE cohort and found that absence of close follow-up, defined as a year or less, was associated with stricture develop after controlling for potential confounding factors. These data are also consistent with our findings [ 11 ].…”
Section: Discussionsupporting
confidence: 94%
“…Second, of the patients who ultimately returned, their follow-up was delayed by an average of 6 months (with the next endoscopy more than a year after the previously scheduled procedure), and when they returned they tended to require higher rates of dilation and lost some esophageal caliber; some had even developed de-novo fibrostenosis. This adds to the emerging literature about EoE disease progression even after diagnosis and may inform discussions about the most appropriate monitoring intervals [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei Patienten, die sich der medizinischen Behandlung entziehen, kommt es zu einer erneuten Krankheitsprogression und steigender Strikturrate 9 . Umgekehrt führt eine engere Nachsorge (alle 12 – 18 Monate) zu einer frühzeitigeren Entdeckung eines histologischen Rezidivs und zu einer niedrigeren Strikturrate 19 .…”
Section: Monitoringunclassified
“…Delay in EoE diagnosis is also associated with increase in stricture in a time-dependent manner ( 20 ). Moreover, while gaps in clinical care of EoE patients are associated with progression to fibrostenosis ( 21 ), close follow-up is associated with a decrease in stricture in EoE patients ( 22 ). Taken together, these findings support the paradigm that chronic EoE inflammation promotes progression to fibrostenosis ( 15 ).…”
Section: Introductionmentioning
confidence: 99%